2013
DOI: 10.1016/j.jval.2013.08.1833
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility Analysis of Disease-Modifying Drugs in Relapsing-Remitting Multiple Sclerosis in Iran

Abstract: BackgroundDisease-modifying drugs (DMDs) are a significant expenditure for treating multiple sclerosis (MS). However, there is limited report on assessment of the cost-utility of DMDs compared with symptom management in the presence of long-term data. This study aimed to assess the lifetime cost-utility from the Iranian healthcare perspectives of 4DMDs relative to symptom management alone in patients with relapsing-remitting multiple sclerosis using evidence from long-term published studies.MethodsA Markov mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 10 publications
3
40
0
Order By: Relevance
“…Hence, the highest costs in treatment with both medications were direct medical costs, in which the largest costs were related to the costs of purchasing the main medicine, which were 64.29% and 46.16%, respectively. The results of the present study are in line with those of the studies conducted by and Nikfar et al, (2013) (24,40).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, the highest costs in treatment with both medications were direct medical costs, in which the largest costs were related to the costs of purchasing the main medicine, which were 64.29% and 46.16%, respectively. The results of the present study are in line with those of the studies conducted by and Nikfar et al, (2013) (24,40).…”
Section: Discussionsupporting
confidence: 92%
“…, using the utility index (QALY) to compare these two medicines, indicated that intramuscular Interferon beta1a (Avonex) was more cost -effective than subcutaneous Interferon beta -1 (Rebif) (21,24,28,45).…”
mentioning
confidence: 99%
“…On the basis of title and abstract, 1168 records were excluded and the remaining 225 records were included for full-text screening. A further 213 articles were excluded at the full-text stage (see Appendix 7 for a list of excluded studies with reasons), leaving 10 studies 154,[264][265][266][267][268][269][270][271][272] that included a decision-analytic model used to estimate the cost-effectiveness of DMTs for treating people with RRMS. …”
Section: Results Of the Searches For Relapsing-remitting Multiple Sclmentioning
confidence: 99%
“…All of the studies included an economic model to estimate the cost-effectiveness of DMTs for treating people with RRMS. The economic evaluations were mainly conducted in the USA 266,267,272 and Spain, 264,268,270 with two studies carried out in Iran 265,269 and the remaining studies carried out in the UK 154 and France. 271 Studies mainly compared IM IFN-β-1a once weekly, SC IFN-β-1a three times weekly, SC IFN-β-1b or SC GA with symptom management.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation